2016
DOI: 10.1245/s10434-016-5115-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical and Molecular Factors Impacting Oncologic Outcomes in Undifferentiated Pleomorphic Sarcoma

Abstract: Background Undifferentiated pleomorphic sarcomas (UPS) present a diagnostic and therapeutic challenge. Identification of prognostic molecular markers is required for the discovery of novel treatment approaches. The aim of this study was to correlate clinicopathologic variables, expression of tyrosine kinase receptors, and markers of cell cycle progression and survival with oncologic outcomes. Methods A tissue microarray containing 208 primary UPS samples was analyzed by immunohistochemistry for protein marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
4
31
1
Order By: Relevance
“…This underlies the need for identification and testing of other immunotherapy methods and targets that may be effective in UPS. Promising markers and therapeutic targets have been identified in UPS and MFS using primary cultures [24,25], and correlation of oncologic outcome and clinicopathologic variables as well as expression of various markers has been also studied [26]. In addition, a small study of 17 patients treated with neoadjuvant radiation therapy prior to resection, immune cell infiltrates and PD-L1 expression were observed to increase with radiation treatment [21].…”
Section: Discussionmentioning
confidence: 99%
“…This underlies the need for identification and testing of other immunotherapy methods and targets that may be effective in UPS. Promising markers and therapeutic targets have been identified in UPS and MFS using primary cultures [24,25], and correlation of oncologic outcome and clinicopathologic variables as well as expression of various markers has been also studied [26]. In addition, a small study of 17 patients treated with neoadjuvant radiation therapy prior to resection, immune cell infiltrates and PD-L1 expression were observed to increase with radiation treatment [21].…”
Section: Discussionmentioning
confidence: 99%
“…No sex predisposition has been described [ 8 ]. Some cases are associated with radiation exposure with other cases not having a strong etiologic link [ 5 , 9 ]. Symptoms are usually nonspecific including weight loss, anorexia, fever, jaundice, malaise, right upper quadrant pain, and palpable abdominal mass [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a number of recurrent chromosomal regions of gain and loss have been identified in soft tissue UPS [ 24 ]. Some of them were reportedly associated with better patient survival [ 9 , 24 ]. Another study [ 25 ] showed that polysomic chromosomes appeared more characteristically in UPS; however, in their study sarcoma-specific chromosomal breaks and oncogene amplifications were rarely identified.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical evaluation of the pAkt in UPS also showed an increased expression of this protein [30]. The high pAkt levels were associated with a poorer disease-specific survival (DSS) outcome, independent of other clinical variables (histological grade, site and depth of the tumor, positive/negative margins, gender and age of patients) and molecular factors (expression of phosphorylated FKHR, phosphorylated ERK1/2, Hepatocyte Growth Factor and C-Met) [30,119,120]. The PTEN gene deletion in UPS is 4% and in MFH is 8% [14] (Figure 2C), suggesting a PTEN-independent activation of the Akt/mTOR pathway [120].…”
Section: Undifferentiated Pleomorphic Sarcoma/myxofibrosarcomamentioning
confidence: 99%
“…The high pAkt levels were associated with a poorer disease-specific survival (DSS) outcome, independent of other clinical variables (histological grade, site and depth of the tumor, positive/negative margins, gender and age of patients) and molecular factors (expression of phosphorylated FKHR, phosphorylated ERK1/2, Hepatocyte Growth Factor and C-Met) [30,119,120]. The PTEN gene deletion in UPS is 4% and in MFH is 8% [14] (Figure 2C), suggesting a PTEN-independent activation of the Akt/mTOR pathway [120]. For example, it cannot be excluded that the oncogenic activation of this pathway can occur through an inappropriate or unregulated activation of the upstream RTKs or by cross-talk of other pathways with members of the Akt/mTOR pathway.…”
Section: Undifferentiated Pleomorphic Sarcoma/myxofibrosarcomamentioning
confidence: 99%